INTERIOR DESIGN CONSIDERATIONS TO ENHANCE STUDENT SATISFACTION IN CLASSROOMS - Bandyopadhyay, Arunabha; George, Aiswarya (PEOPLE: International Journal of Social Sciences, 2020)
The built environment that humans live in, affects them in their cognitive, emotional and social terms. Every building has a specific purpose to serve. School buildings being the vital infrastructure to impart education, needs to be designed in ways that they provide high quality learning environment. The architectural and interior design considerations in schools may impact the learning ability, productivity and creativity of the students. To start with, the satisfaction of the students must be taken into consideration. This study comprises of exploratory research from previously done studies on similar fields, making an attempt to find out the architectural aspects necessary to be considered while designing classrooms in schools. Surveys have been conducted in schools in India to record the students’ perception of satisfaction in terms of classroom design. The final result of this study deduces a set of interior design rules which may be followed in classroom design satisfying the student user group. This study can work as an inception to other advanced studies such as linking performance of students with interior design of classrooms.